DEDENG CERITA RAKYAT LANGKAT KAJIAN ANTROPOLOGIS - Syafna Elvira Utami; Nurelide Nurelide; Arianto Arianto (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2022)
This study aims to describe the theme, setting, character, and cultural values. The object of research is a folk tale from the North Sumatra Province Language Center published in 2020. Data collection uses repeated reading and recording techniques. The data analysis technique is descriptive qualitative. The approach used is a literary anthropological approach. Research findings (1) The theme of Dedeng's story is "Forbidden Love". Because these lovers are siblings. (2) The setting of Dedeng's story has a place setting, time setting, and atmosphere setting. The setting in Dedeng's story is the island, the hut, the flower garden, the beach, the sea. The time setting in Dedeng's story is during the day. And the setting of the atmosphere in Dedeng's story is sad and touching. (3) The characters from Dedeng's story are Dedeng, Putri Bulan, Datuk Father of Putri Bulan, Mak Surgeon, Panglima Datuk Pulau Kampai, and Guards. (4) The cultural values of Dedeng's story are, his father is a descendant of Datuk and replaces his grandfather's position, sings poetry and rhymes, nobles cannot marry ordinary people, sings poetry of broken hearts, Kampai Island people who join in singing poetry as Dedeng. (5) The educational value of Dedeng's story is to work diligently and be devoted to parent.